Adhesive resin composition and film

The adhesive resin composition, comprising specific proportions of propylene polymer, modified polyolefin, and ethylene polymer, addresses the adhesion reduction issue in lithium-ion battery packaging films and electrode sealing materials by providing excellent electrolyte resistance.

JP7657939B2Active Publication Date: 2025-04-07MITSUI CHEMICALS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023542423
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-18
Filing Date
2022-08-17
Publication Date
2025-04-07
Estimated Expiration
2042-08-17

AI Technical Summary

Technical Problem

The packaging film for lithium-ion batteries faces a reduction in adhesion between the adhesive polyolefin film and the metal foil when immersed in electrolyte solution, leading to insufficient electrolyte resistance.

Method used

An adhesive resin composition comprising 50 to 89.9 parts by mass of propylene polymer (A), 0.1 to 20 parts by mass of modified polyolefin (B), and 10 to 30 parts by mass of ethylene polymer (C), which forms a battery packaging film and electrode sealing material with excellent electrolyte resistance.

Benefits of technology

The adhesive resin composition effectively maintains high adhesion strength even after immersion in electrolyte solution, ensuring excellent electrolyte resistance for battery packaging films and electrode sealing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657939000001
    Figure 0007657939000001
Patent Text Reader

Abstract

An adhesive resin composition including: 50-89.9 parts by mass of a propylene polymer (A) that satisfies (a1) and (a2) below; 0.1-20 parts by mass of a modified polyolefin (B); and 10-30 parts by mass of an ethylene polymer (C) that satisfies (c1)-(c3) below (the total of (A)-(C) being 100 parts by mass). (a1) Includes a propylene polymer (a-1) that has a melting point greater than or equal to 120°C, and a propylene polymer (a-2) that has a melting point less than 120°C. (a2) The proportion of (A) that (a-1) accounts for is 50-70.0 mass%. (c1) Includes an ethylene homopolymer (c-1) and an ethylene / α-olefin copolymer (c-2). (c2) The MFR is 0.1-10 g / 10 min. (c3) The proportion of (C) that (c-1) accounts for is 40-100 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive resin composition and a film using the same. [Background technology]

[0002] In recent years, the fields in which lithium-ion batteries are used have expanded to include portable electronic devices, automobiles, etc. Unlike the conventionally used metal cans, lithium-ion batteries are now being packaged in laminated packaging materials made of lightweight aluminum foil laminated with a resin film in a bag shape to accommodate the flexibility of battery shape and miniaturization.

[0003] In addition, in lithium-ion batteries, the ends of the metal foil are heat-sealed with an adhesive polyolefin film to bond the metal foil together and ensure insulation.

[0004] Patent Document 1 describes a packaging material for batteries which includes at least a base layer, a metal foil layer having a chemical conversion coating layer on at least one side thereof, an acid-modified polyolefin layer, and a heat seal layer consisting of a high melting point polypropylene layer and an ethylene-propylene random copolymer layer, laminated in this order, wherein the high melting point polypropylene layer is disposed closer to the metal foil layer than the ethylene-propylene random copolymer layer and has a melting point of 150°C or higher. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-273398 A Summary of the Invention [Problem to be solved by the invention]

[0006] Packaging films for lithium-ion batteries have the problem that the adhesive strength between the adhesive polyolefin film and the metal foil decreases when immersed in an electrolyte solution. It is necessary that this adhesive strength does not decrease (hereinafter referred to as "electrolyte resistance"). However, the battery packaging film described in Patent Document 1 had insufficient electrolyte resistance.

[0007] Furthermore, in lithium ion batteries, there is an adhesive polyolefin film called an electrode sealant that bonds the electrodes together, and this adhesive polyolefin film is also required to be resistant to the electrolyte.

[0008] The present invention aims to provide an adhesive resin composition capable of forming a packaging film for batteries and an electrode sealant for lithium ion batteries that have excellent electrolyte resistance, and a single-layer or multilayer film that exhibits excellent electrolyte resistance when used in a packaging film for batteries and an electrode sealant for lithium ion batteries. [Means for solving the problem]

[0009] The present invention relates to, for example, the following [1] to

[11] .

[0010] [1] 50 to 89.9 parts by mass of a propylene-based polymer (A) satisfying the following (a1) and (a2), 0.1 to 20 parts by mass of a modified polyolefin (B) obtained by modifying a polyolefin (b) with an unsaturated carboxylic acid and / or a derivative thereof, and 10 to 30 parts by mass of an ethylene polymer (C) satisfying the following (c1) to (c3) (wherein the total of (A), (B) and (C) is 100 parts by mass): The adhesive resin composition comprises:

[0011] (a1) Contains a propylene polymer (a-1) having a melting point (Tm) of 120°C or higher as measured by differential scanning calorimetry, and a propylene polymer (a-2) having a melting point (Tm) of less than 120°C or no melting point is measured.

[0012] (a2) The proportion of the propylene polymer (a-1) in the propylene polymer (A) is 50 to 70.0% by mass.

[0013] (c1) It contains (c-1) a copolymer of ethylene and at least one kind of α-olefin selected from α-olefins having 3 to 20 carbon atoms, and optionally (c-2) an ethylene homopolymer.

[0014] (c2) The melt flow rate measured in accordance with ASTM D1238 at 190° C. under a load of 2.16 kg is 0.1 to 10 g / 10 min.

[0015] (c3) The proportion of the copolymer (c-1) in the ethylene polymer (C) is 40 to 100% by mass.

[0016] [2] The adhesive composition according to the above [1], wherein the content of the ethylene polymer (C) is 12.5 to 30 parts by mass.

[0017] [3] The adhesive resin composition according to [1] or [2], wherein the melt flow rate (MFR) of the copolymer (c-1) measured in accordance with ASTM D1238 at 230°C under a load of 2.16 kg is less than 6.0 g / 10 min.

[0018] [4] the polyolefin (B) contains a structure derived from the unsaturated carboxylic acid and / or a derivative thereof in an amount of 0.01 to 5 mass % calculated as a structure derived from maleic anhydride, The adhesive resin composition according to any one of the above [1] to [3], wherein the polyolefin (b) contains 90 to 100 mol % of structural units derived from propylene.

[0019] [5] The adhesive resin composition according to any one of [1] to [4] above, which has a melt flow rate of less than 7.0 g / 10 min, measured at 230° C. under a load of 2.16 kg in accordance with ASTM D1238.

[0020] [6] A single-layer or multi-layer film comprising at least one layer containing the adhesive resin composition according to any one of [1] to [5] above.

[0021] [7] A multilayer film comprising at least one layer comprising any one of the adhesive resin compositions [1] to [5] above, and at least one other layer which is a layer other than the layer comprising the adhesive resin composition, wherein the layer comprising the adhesive resin composition is in contact with the other layer.

[0022] [8] A multilayer film comprising at least one layer containing the adhesive resin composition according to any one of [1] to [5] above, and at least one layer selected from a metal-containing layer, a polyolefin layer, and a polar resin layer, wherein the layer containing the adhesive resin composition is in contact with the layer selected from the metal-containing layer, the polyolefin layer, and the polar resin layer.

[0023] [9] The monolayer or multilayer film according to any one of [6] to [8] above, which is a battery packaging film.

[0024]

[10] The single-layer or multilayer film according to any one of [6] to [8] above, which is an electrode sealing material for a lithium-ion battery.

[0025]

[11] A method for producing a monolayer or multilayer film, comprising a step of melt-extrusion molding the adhesive resin composition according to any one of the above [1] to [5]. Effect of the Invention

[0026] According to the adhesive resin composition of the present invention, it is possible to form a packaging film for batteries and an electrode sealant for lithium ion batteries that have excellent electrolyte resistance.

[0027] The single-layer or multi-layer film according to the present invention exhibits excellent electrolyte resistance when used as a packaging film for batteries and an electrode sealant for lithium ion batteries. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The present invention will now be described in further detail.

[0029] [Adhesive resin composition] The adhesive resin composition according to the present invention contains a propylene-based polymer (A), a modified polyolefin (B) and an ethylene-based polymer (C).

[0030] <Propylene-based polymer (A)> The propylene polymer (A) is a propylene polymer that satisfies the requirements (a1) and (a2) described below.

[0031] The requirement (a1) is that the propylene polymer (A) contains a propylene polymer (a-1) having a melting point (Tm) of 120°C or higher as measured by differential scanning calorimetry, and a propylene polymer (a-2) having a melting point (Tm) of less than 120°C or no melting point is measured.

[0032] (Propylene-based polymer (a-1)) The propylene polymer (a-1) may be a propylene homopolymer or a copolymer of propylene and at least one α-olefin other than propylene having 2 to 20 carbon atoms. Examples of the α-olefin other than propylene having 2 to 20 carbon atoms include ethylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, and ethylene or an α-olefin having 4 to 10 carbon atoms is preferred.

[0033] The copolymer of propylene and these α-olefins may be a random copolymer or a block copolymer. The structural units derived from these α-olefins may be contained in the copolymer of α-olefins and propylene at a ratio of 35 mol% or less, preferably 30 mol% or less, more preferably 10 mol% or less, and even more preferably 5 mol% or less. The structural units may be contained in the copolymer of α-olefins and propylene at a ratio of 1 mol% or more, more preferably 2 mol% or more.

[0034] The propylene polymer (a-1) has a melting point (Tm) of 120° C. or higher as measured by differential scanning calorimetry under the following conditions.

[0035] The melting point (Tm) is preferably 120 to 170°C, more preferably 130 to 165°C.

[0036] (Measurement conditions) The melting point (Tm) is measured using a differential scanning calorimeter (DSC) (e.g., PerkinElmer DSC8500 device). Approximately 5 mg of the sample is sealed in an aluminum pan to prepare the sample. The temperature profile is as follows: increase the temperature from room temperature to 230°C at 10°C / min, hold at 230°C for 10 minutes, then decrease the temperature to 30°C at 10°C / min, hold at 30°C for 1 minute, and increase the temperature to 230°C at 10°C / min. The peak temperature during the second temperature increase (if there are multiple peak temperatures, the highest peak temperature) is taken as the melting point (Tm).

[0037] The propylene polymer (a-1) may have either an isotactic structure or a syndiotactic structure.

[0038] That is, the form of the propylene polymer (a-1) includes an isotactic propylene polymer (a-11) and a syndiotactic propylene polymer (a-12).

[0039] Examples of the isotactic propylene polymer (a-11) include homopolypropylenes having excellent heat resistance, such as known homopolypropylenes having a copolymerization component other than propylene of 3 mol % or less, block polypropylenes having an excellent balance between heat resistance and flexibility, such as known block polypropylenes having a normal decane-eluted rubber component of 3 to 30 mass %, and random polypropylenes having an excellent balance between flexibility and transparency, such as known random polypropylenes having a melting peak of 120°C or higher, preferably 130°C to 150°C, as measured by a differential scanning calorimeter (DSC). These can be appropriately selected to obtain the desired physical properties, or two or more of the above polypropylene components having different melting points or rigidities can be used in combination.

[0040] Such an isotactic propylene polymer (a-11) can be produced, for example, by polymerizing propylene or copolymerizing propylene with another α-olefin using a Ziegler catalyst system consisting of a solid catalyst component containing magnesium, titanium, a halogen and an electron donor as essential components, an organoaluminum compound and an electron donor, or a metallocene catalyst system using a metallocene compound as one of the catalyst components.

[0041] The syndiotactic propylene polymer (a-12) contains 90 mol % or more of structural units derived from propylene and 10 mol % or less of structural units derived from one or more selected from ethylene and α-olefins having 4 to 20 carbon atoms, and preferably contains 91 mol % or more of structural units derived from propylene and 9 mol % or less of structural units derived from one or more selected from ethylene and α-olefins having 4 to 20 carbon atoms (the total of both structural units is 100 mol %).

[0042] Examples of α-olefins having 4 to 20 carbon atoms include 1-butene, 3-methyl-1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0043] The syndiotactic propylene polymer (a-12) can be produced, for example, by a method such as that described in International Publication No. WO2011 / 078054.

[0044] (Propylene-based polymer (a-2)) The propylene polymer (a-2) has a melting point (Tm) of less than 120° C. as measured by differential scanning calorimetry under the above conditions, or is a propylene polymer that has no melting point as measured by differential scanning calorimetry.

[0045] The propylene polymer (a-2) has structural units derived from propylene and at least one olefin selected from α-olefins having 2 to 20 carbon atoms other than propylene, and the content of structural units derived from at least one α-olefin selected from α-olefins having 2 to 20 carbon atoms other than propylene is usually 30 mol% or less, preferably 5 to 30 mol%, more preferably 7 to 26 mol%, and even more preferably 10 to 20 mol%. The content of structural units derived from propylene is preferably 74 to 93 mol%, and more preferably 80 to 90 mol%.

[0046] The propylene polymer (a-2), 13 The isotactic triad fraction (mm fraction) measured by C-NMR is usually 80% or more, and preferably 85% or more. When the isotactic triad fraction (mm) is in the above range, it is preferable in terms of maintaining mechanical properties.

[0047] Examples of the α-olefins having 2 to 20 carbon atoms other than propylene include ethylene, 3-methyl-1-butene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. As the at least one olefin selected from the α-olefins having 2 to 20 carbon atoms other than propylene, particularly preferred are ethylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene.

[0048] (Other requirements) The propylene copolymer (a-2) has an intrinsic viscosity [η] of 0.1 to 10 dL / g, preferably 0.5 to 10 dL / g, as measured in decalin at 135° C. The crystallinity of the propylene copolymer (a-2) measured by X-ray diffraction is preferably 20% or less, more preferably 0 to 15%.

[0049] This propylene-based copolymer (a-2) has a single glass transition temperature, and the glass transition temperature (Tg) obtained by differential scanning calorimetry (DSC) is usually in the range of -50°C to 10°C, preferably -40°C to 0°C, and more preferably -35°C to 0°C.

[0050] The molecular weight distribution (Mw / Mn, polystyrene equivalent, Mw: weight average molecular weight, Mn: number average molecular weight) of the propylene copolymer (a-2) measured by GPC is preferably 3.5 or less, more preferably 3.0 or less, and even more preferably 2.5 or less. The lower limit is, for example, 1.5 or more.

[0051] The requirement (a2) is that the proportion of the propylene polymer (a-1) in the propylene polymer (A) is 50 to 70.0 mass %. When the proportion of the polymer (a-1) is within the above range, a composition having excellent whitening resistance can be obtained.

[0052] The propylene polymer (A) desirably has a melt flow rate (MFR) measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg in the range of 0.01 to 1000 g / 10 min, preferably 0.05 to 100 g / 10 min.

[0053] <Modified polyolefin (B)> The modified polyolefin (B) is a polyolefin (b) modified with an unsaturated carboxylic acid and / or a derivative thereof.

[0054] A preferred example of the polyolefin (b) is polypropylene (b1).

[0055] The polypropylene (b1) is, for example, a propylene homopolymer and / or a propylene-α-olefin copolymer. The α-olefin is not limited, but preferably includes ethylene and α-olefins having 4 to 20 carbon atoms, and these α-olefins may be used alone or in combination of two or more. Preferred α-olefins are ethylene and α-olefins having 4 to 10 carbon atoms, and among these, ethylene and α-olefins having 4 to 8 carbon atoms are particularly suitable. Here, the content of structural units derived from propylene in the propylene-α-olefin copolymer is at least 50 mol % or more and less than 100%.

[0056] The polypropylene (b1) preferably has an intrinsic viscosity [η] of 0.1 to 10 dl / g. When the intrinsic viscosity [η] is in this range, a composition having excellent moldability and mechanical strength can be obtained.

[0057] The method for producing the polypropylene (b1) is not particularly limited, and examples thereof include well-known methods using well-known catalysts such as Ziegler-Natta catalysts and metallocene catalysts.

[0058] The polypropylene (b1) is preferably a crystalline polymer, and in the case of a copolymer, it may be a random copolymer or a block copolymer. The polypropylene (b1) may be a commercially available product.

[0059] The polypropylene (b1) may be, for example, a homopolypropylene or a propylene-α-olefin random copolymer, or may contain several different isotactic polypropylenes.

[0060] Examples of the unsaturated carboxylic acid and / or its derivative include an unsaturated compound having one or more carboxy groups in one molecule, an ester of a compound having a carboxy group and an alkyl alcohol, and an unsaturated compound having one or more structures represented by R-CO-O-CO-R' (R and R' are each independently a hydrocarbon group) in one molecule. Examples of the unsaturated group in the unsaturated compound include a vinyl group, a vinylene group, and an unsaturated cyclic hydrocarbon group. The unsaturated carboxylic acid and / or its derivative may be used alone or in combination of two or more. Among these, unsaturated dicarboxylic acids and their acid anhydrides are preferred, and maleic acid, nadic acid, and their acid anhydrides are particularly preferred.

[0061] The amount of the structure derived from the unsaturated carboxylic acid and / or its derivative in the modified polyolefin (B) is preferably 0.01 to 5 mass%, more preferably 0.05 to 3.5 mass%, calculated as the amount of the structure derived from maleic anhydride (i.e., assuming that the unsaturated carboxylic acid and / or its derivative is maleic anhydride). When the amount of the structure derived from the unsaturated carboxylic acid and / or its derivative is within the above range, a resin composition having a good balance between moldability and adhesiveness can be obtained.

[0062] In the modified polyolefin (B), the polyolefin (b) preferably contains 50 to 100 mol % of structural units derived from propylene. When the content ratio of the structural units derived from propylene is within the above range, a resin composition having excellent heat resistance can be obtained.

[0063] The method of modifying the polyolefin (b) with an unsaturated carboxylic acid and / or its derivative is not particularly limited, and any conventionally known graft polymerization method such as a solution method, a melt kneading method, etc., can be used. For example, there is a method of melting the polyolefin (b) and adding an unsaturated carboxylic acid and / or its derivative thereto for graft reaction, or a method of dissolving the polyolefin (b) in a solvent to prepare a solution and adding an unsaturated carboxylic acid and / or its derivative thereto for graft reaction.

[0064] <Ethylene-based polymer (C)> The ethylene polymer (C) is an ethylene polymer that satisfies the following requirements (c1) to (c3).

[0065] The requirement (c1) is that the ethylene-based polymer (C) contains a copolymer (c-1) of ethylene and at least one α-olefin selected from α-olefins having 3 to 20 carbon atoms, and optionally an ethylene homopolymer (c-2).

[0066] Examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. Among these, propylene, 1-butene, 1-hexene, and 1-pentene are preferred.

[0067] The α-olefin may be one type or two or more types.

[0068] The copolymer (c-1) preferably contains 30 to 99 mol %, preferably 50 to 99 mol %, of structural units derived from ethylene, and 1 to 70 mol %, preferably 1 to 50 mol %, of structural units derived from an α-olefin selected from α-olefins having 3 to 20 carbon atoms (the total of both being 100 mol %).

[0069] The melt flow rate (MFR) of the copolymer (c-1) measured in accordance with ASTM D1238 at 230°C under a load of 2.16 kg is preferably less than 6.0 g / 10 min, more preferably from 0.5 to 5.5 g / 10 min, and even more preferably from 0.5 to 2.0 g / 10 min.

[0070] The melt flow rate (MFR) of the copolymer (c-1) measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg is preferably less than 4.5 g / 10 min, more preferably from 0.3 to 4.1 g / 10 min, and even more preferably from 0.3 to 1.5 g / 10 min.

[0071] The requirement (c2) is that the melt flow rate (MFR) of the ethylene polymer (C) measured in accordance with ASTM D1238 at 190° C. under a load of 2.16 kg is from 0.1 to 10 g / 10 min.

[0072] The MFR is preferably 0.3 to 8 g / 10 min, more preferably 0.5 to 6 g / 10 min. When the MFR is in the above range, the composition of the present invention has a good balance between flexibility and mechanical strength, and has high adhesive strength.

[0073] On the other hand, if the MFR exceeds 10 g / 10 min, the composition will undergo significant wall loss during heat sealing, and the adhesive layer formed from the composition will become thinner, resulting in a decrease in its adhesive strength. If the MFR is below 0.1 g / 10 min, the wettability to the adherend will decrease, resulting in a decrease in adhesive strength.

[0074] The density of the ethylene polymer (C) is preferably 0.855 to 0.970 g / cm from the viewpoint of flexibility. 3 , more preferably 0.860 to 0.940 g / cm 3 , and more preferably 0.865 to 0.930 g / cm 3 is in the range.

[0075] The requirement (c3) is that the proportion of the copolymer (c-1) in the ethylene polymer (C) is 40 to 100 mass %. From the viewpoint of electrolyte resistance, the proportion is preferably 45 to 100 mass %, more preferably 50 to 100 mass %.

[0076] The method for producing the copolymer (c-1) and homopolymer (c-2) is not particularly limited, and they can be produced by a known method using a known catalyst such as a high-pressure method, a Ziegler-Natta catalyst, a metallocene catalyst, etc. The copolymer (c-1) and homopolymer (c-2) may be commercially available products.

[0077] The ethylene polymer (C) may be one to which a small amount of maleic anhydride, etc. is grafted, so long as the above conditions are satisfied. In addition, the ethylene polymer (C) may be one to which a small amount of maleic anhydride, etc. is grafted, and then the graft monomer is further modified with a diamine, a carbodiimide, etc., so long as the above conditions are satisfied.

[0078] <Optional ingredients> The adhesive resin composition of the present invention may contain additives within the range that does not impair the effects of the present invention. Examples of additives include antioxidants, ultraviolet absorbers, neutralizing agents, nucleating agents, light stabilizers, antistatic agents, antiblocking agents, lubricants, odor absorbents, antibacterial agents, moisture absorbents, pigments, inorganic or organic fillers, and polymers other than the propylene polymer (A), modified polyolefin (B), and ethylene polymer (C).

[0079] (Adhesive resin composition) The contents of the propylene-based polymer (A), the modified polyolefin (B), and the ethylene-based polymer (C) in the adhesive resin composition of the present invention are 50 to 89.9 parts by mass, 0.1 to 20 parts by mass, and 10 to 30 parts by mass, respectively, based on 100 parts by mass of the total content of these three components, preferably 50 to 87.5 parts by mass, 0.5 to 20 parts by mass, and 12 to 30 parts by mass, respectively, and more preferably 50 to 84 parts by mass, 1 to 20 parts by mass, and 15 to 30 parts by mass, respectively.

[0080] When the content of the above components is within the above range, the resin composition of the present invention has high adhesion, particularly adhesion after immersion in an electrolyte solution, and a film including a layer obtained from the composition of the present invention is less likely to experience a decrease in adhesion due to immersion in an electrolyte solution.

[0081] If the content of the propylene polymer (A) is less than 50 parts by mass, a desired initial adhesive strength cannot be obtained.

[0082] It is also a preferred embodiment that the content of the ethylene polymer (C) is 12.5 to 30 parts by mass or 13 to 30 parts by mass. When the content of the ethylene polymer (C) is within the above range, the adhesive resin composition is less likely to have a decrease in adhesion due to immersion in an electrolytic solution, and the adhesive resin composition has excellent stability during film formation.

[0083] The adhesive resin composition of the present invention preferably has an MFR (based on ASTM D1238, 190°C, 2.16 kg load) of less than 7.0 g / 10 min, more preferably 3.0 g / 10 min or more and less than 7.0 g / 10 min. When the MFR is in the above range, the adhesive resin composition of the present invention has a good balance between moldability (resistance to wall thinning) and adhesiveness.

[0084] The amount of the structure derived from the unsaturated carboxylic acid and / or its derivative in the adhesive resin composition of the present invention is preferably 0.03 to 0.30 mass%, more preferably 0.06 to 0.20 mass%, calculated as the amount of the structure derived from maleic anhydride (i.e., assuming that the unsaturated carboxylic acid and / or its derivative is maleic anhydride).

[0085] The adhesive resin composition of the present invention can be produced by a conventional method, except that the propylene-based polymer (A), the modified polyolefin (B), and the ethylene-based polymer (C) are used as raw materials, for example, by melt-kneading the above-mentioned components.

[0086] <Sea-island structure> The adhesive resin composition of the present invention forms a finely dispersed structure (so-called sea-island structure) containing the propylene-based polymer (A) in a continuous phase and the ethylene-based copolymer (C) dispersed in the continuous phase in a dispersed phase. By forming such a structure, the electrolyte resistance of the layer made of the adhesive resin composition is improved. Although the reason for this is not necessarily clear, it is presumed that the electrolyte is trapped in the dispersed phase, thereby suppressing the electrolyte from penetrating into the interface (hereinafter also referred to as the "adhesive interface") between the layer made of the adhesive resin composition and the metal.

[0087] The average particle size of the dispersed phase, measured by the following method, is preferably 0.001 to 10 μm. The upper limit of the average particle size of the dispersed phase is more preferably 8 μm, further preferably 6 μm, and particularly preferably 5 μm, and the lower limit is preferably 0.09 μm.

[0088] (Method of measuring average particle size) The test piece is ground with a microtome or the like, and an arbitrary cross section of about 45 μm × 75 μm or more obtained is analyzed at 3000 times magnification using a transmission electron microscope (e.g., H-7650 manufactured by Hitachi High-Technologies Corporation). The analysis is performed by binarizing the image using image analysis software (e.g., ImageJ).

[0089] From the TEM photograph, the areas occupied by the continuous phase and the dispersed phase are identified.

[0090] When the shape of the dispersed phase is a circle, the diameter is taken as the particle size, and when the shape of the dispersed phase is an ellipse, the length of the major axis is taken as the particle size. When the shape is other than a circle or an ellipse, the area of ​​the dispersed phase is calculated, and the diameter of a perfect circle with the same area is calculated and taken as the particle size.

[0091] When the average particle size of the dispersed phase is 0.001 μm or more, a sufficient cavitation effect is obtained, and the electrolyte resistance is good.

[0092] When the average particle size of the dispersed phase is 10 μm or less, the dispersed phase does not inhibit the adhesiveness of the continuous phase when present at the adhesive interface, and the composition of the present invention exhibits good adhesiveness.

[0093] In a randomly selected 10 μm×10 μm region on the cross section of a test piece when measuring the average particle size of the dispersed phase of the adhesive resin composition of the present invention, the ratio of the number of dispersed phases having a particle size of 0.001 to 5 μm, which is 80% or more of the total number of dispersed phases, is preferably 80% or more, more preferably 85% or more, even more preferably 90% or more, particularly preferably 95% or more, and most preferably 100%. When the ratio is 85% or more, the composition has excellent adhesiveness.

[0094] [Single layer or multi-layer film] The monolayer or multilayer film of the present invention is characterized by comprising at least one layer containing the above-mentioned adhesive resin composition of the present invention.

[0095] Examples of specific embodiments of the monolayer or multilayer film of the present invention include: A multilayer film comprising at least one layer containing the adhesive resin composition of the present invention and at least one other layer which is a layer other than the layer containing the adhesive resin composition, the layer containing the adhesive resin composition being in contact with the other layer; and A multilayer film comprising at least one layer containing the adhesive resin composition of the present invention and at least one layer selected from a metal-containing layer, a polyolefin layer and a polar resin layer, wherein the layer containing the adhesive resin composition is in contact with at least one layer selected from the metal-containing layer, the polyolefin layer and the polar resin layer. Examples include:

[0096] The other layers include a metal-containing layer, a polyolefin layer, and a polar resin layer.

[0097] Examples of the metal-containing layer include an aluminum layer (for example, aluminum foil), a copper layer, and a stainless steel layer.

[0098] Examples of the polyolefin layer include a polypropylene layer, a poly-4-methylpentene layer, and a polyethylene layer.

[0099] Examples of the polar resin layer include a polyamide layer, an EVOH layer, a PET layer, and a PBT layer.

[0100] The layer containing the adhesive resin composition of the present invention can be produced by molding the adhesive resin composition of the present invention, for example, by melt extrusion molding. Thus, the monolayer or multilayer film of the present invention can be produced by a casting method, an inflation method, an extrusion lamination method, or the like.

[0101] The monolayer or multilayer film of the present invention can be preferably used as a packaging film for batteries, such as a packaging film for lithium batteries, or as an electrode sealant for lithium ion batteries. EXAMPLES

[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0103] [Method of measuring physical properties] <Melt flow rate (MFR)> The MFR of the propylene-based polymer and the composition was measured in accordance with ASTM D1238 at a temperature of 230° C. and a load of 2.16 kg.

[0104] The MFR of the ethylene polymer was measured according to ASTM D1238 at a temperature of 190°C and a load of 2.16 kg, or at a temperature of 230°C and a load of 2.16 kg. When the ethylene polymer contains two or more types of copolymer (c-1) and ethylene homopolymer (c-2), the "MFR of the ethylene polymer" refers to a value calculated from the MFR of each ethylene polymer by the logarithmic additivity rule.

[0105] <density> The density was measured in accordance with JIS K7112 (density gradient tube method).

[0106] <Content of structural units> The content ratio of structural units derived from ethylene or propylene in a polymer is quantified by 13 C-NMR was performed using the following equipment and conditions.

[0107] A JECX400P nuclear magnetic resonance spectrometer manufactured by JEOL Ltd. was used. A mixed solvent of heavy orthodichlorobenzene / heavy benzene (80 / 20% by volume) was used as the solvent. The sample concentration was 60 mg / 0.6 mL, the measurement temperature was 120 °C, and the observation nuclei were 13 The conditions used were: C (100 MHz), sequence: single pulse proton decoupling, pulse width: 4.62 μs (45° pulse), repetition time: 5.5 s, number of accumulations: 8000, and chemical shift reference value: 29.73 ppm.

[0108] <Amount of graft modification> The amount of the structure derived from maleic anhydride (graft modification amount) was determined by an infrared absorption analyzer by measuring the 1790 cm -1 The peak intensity was measured and quantified using a previously prepared calibration curve.

[0109] [Raw materials] The polyolefins used in the examples and comparative examples are shown below. All of these polyolefins were prepared by polymerization and, optionally, graft modification with maleic anhydride according to a conventional method. Propylene polymer (A) PP-1: Random polypropylene (propylene content 96 mol%, ethylene content 4 mol%, MFR = 7.0 g / 10 min, density = 0.91 g / cm 3 , melting point = 138°C, isotactic structure) PP-2: Random polypropylene (propylene content 96 mol%, ethylene content 4 mol%, MFR = 29.0 g / 10 min, density = 0.90 g / cm 3 , melting point = 138°C, isotactic structure) PER-1: Propylene ethylene copolymer (propylene content 87 mol%, ethylene content 13 mol%, MFR = 8.0 g / 10 min, density = 0.88 g / cm 3 , melting point = 79°C) Polyolefin (B) Modified PP-1: Modified homopolypropylene (amount of structure derived from maleic anhydride (graft modification amount): 3.0% by mass) Ethylene polymer (C) EPR-1: Ethylene-propylene copolymer (ethylene content 80 mol%, propylene content 20 mol%, MFR = 0.6 g / 10 min at 190°C and 2.16 kg load, MFR = 0.8 g / 10 min at 230°C and 2.16 kg load, density = 0.87 g / cm 3 ) PE-1: Low-density polyethylene (MFR = 7.0 g / 10 min at 190°C and 2.16 kg load, MFR = 17.8 g / 10 min at 230°C and 2.16 kg load, density = 0.91 g / cm 3 ) [Example 1] <Preparation of Composition 1> Composition 1 was obtained by melt-kneading 48 parts by mass of PP-1, 25 parts by mass of PER-1, 5 parts by mass of modified PP-1, 15 parts by mass of EPR-1, and 7 parts by mass of PE-1 at 230°C using a single-screw extruder.

[0110] <Production of the Complex> A film having a thickness of 100 μm was formed from the composition 1 obtained in Example 1 using an extrusion molding machine equipped with a T-die. The obtained film was overlapped with an aluminum foil having a thickness of 200 μm, and heat-sealed for 5 seconds using a heat sealer under conditions of 160° C. and 0.1 MPa. The obtained composite was cut into a width of 15 mm to prepare a measurement sample.

[0111] <Immersion of the composite in electrolyte> One of the measurement samples was immersed in an electrolyte solution containing 1 mol / L LiPF6 in a solvent of ethyl carbonate:diethyl carbonate = 3:7 with 1000 ppm water added, and left to stand at 85°C for one week.

[0112] <Adhesive strength measurement of composite> For the other measurement samples (composites immediately after production) and the measurement samples after immersion in the electrolyte (composites after immersion in the electrolyte), the adhesive strength (unit: N / 15 mm) between the aluminum foil and the film made of Composition 1 was measured at room temperature of 23°C by the T-peel method using a tensile tester. The crosshead speed was 300 mm / min. The adhesive strength of the composite after immersion in the electrolyte (hereinafter also referred to as "adhesive strength after immersion in the electrolyte") was scored according to the ratio of the adhesive strength of the composite immediately after production (hereinafter also referred to as "initial adhesive strength"), and the results are shown in Table 1. The evaluation criteria are as follows.

[0113] (Initial adhesive strength) CC: Less than 8N / 15mm BB: 8N / 15mm or more, less than 10N / 15mm AA:10N / 15mm or more (Electrolyte resistance) CC: Adhesion strength after immersion in electrolyte / initial adhesion strength is less than 10% BB: Adhesion strength after immersion in electrolyte / initial adhesion strength is 10% or more but less than 15% AA: Adhesion strength after immersion in electrolyte / initial adhesion strength is 15% or more Incidentally, "-" indicates that the electrolyte resistance was not evaluated.

[0114] <Evaluation of composition's thinning effect> A film having a thickness of 100 μm was formed from the composition 1 obtained in Example 1 using an extrusion molding machine equipped with a T-die. Two of the obtained films were stacked and heat-sealed for 3 seconds using a heat sealer under conditions of 170° C. and 0.2 MPa. The cross section of the heat-sealed portion was observed under a microscope, and the thickness of the thinnest portion was measured and recorded as the thickness after heat sealing. The remaining rate after heat sealing was calculated by (thickness after heat sealing) / (initial thickness of two films), and a score was assigned according to the remaining rate, as shown in Table 1. The evaluation criteria are as follows.

[0115] (Resistance to thinning) CC: Thickness after heat sealing / initial thickness is less than 30% BB: Thickness after heat sealing / initial thickness is 30% or more and less than 60% AA: Thickness after heat sealing / initial thickness is 60% or more <Evaluation of whitening resistance of composition> PP-2 and composition 1 were co-extruded at 290°C using a screw with a diameter of 50 mm and an effective length L / D of 28. The extruded PP-2 and composition 1 were laminated in a feed block so that PP-2 was the outer layer and composition 1 was the inner layer, and a film-like laminate with a thickness of about 40 μm and both the outer layer and the inner layer were 20 μm was produced. The die temperature was 290°C. This laminate was brought into contact with the surface of an aluminum foil (thickness 20 μm) in a molten state, and then taken up at a speed of 50 m / min while being cooled by a chill roll with a pinch roll. The obtained multilayer film was deep-draw molded in a mold with a meshing depth of 5 mm. The degree of whitening that occurred on the wall surface of the obtained molded body was visually evaluated according to the following criteria.

[0116] AA: No whitening BB: Slightly bleached CC: Significantly white [Examples 2 and 3, Comparative Examples 1 to 6] A composition was prepared in the same manner as in Example 1, except that the composition was prepared according to the formulation shown in Table 1, and a composite or the like was produced using the obtained composition and evaluated. The results are shown in Table 1.

[0117] [Table 1]

Claims

1. 50 to 89.9 parts by mass of a propylene-based polymer (A) satisfying the following (a1) and (a2), 0.1 to 20 parts by mass of a modified polyolefin (B) obtained by modifying a polyolefin (b) with an unsaturated carboxylic acid and / or a derivative thereof, and 10 to 30 parts by mass of an ethylene polymer (C) satisfying the following (c1) to (c3) (wherein the total of (A), (B) and (C) is 100 parts by mass). and having a melt flow rate of less than 7.0 g / 10 min as measured at 230° C. under a load of 2.16 kg in accordance with ASTM D1238. (a1) Contains a propylene polymer (a-1) having a melting point (Tm) of 120° C. or higher as measured by differential scanning calorimetry, and a propylene polymer (a-2) having a melting point (Tm) of less than 120° C. or no melting point is measured. (a2) The proportion of the propylene polymer (a-1) in the propylene polymer (A) is 50 to 70.0% by mass. (c1) It contains (c-1) a copolymer of ethylene and at least one α-olefin selected from α-olefins having 3 to 20 carbon atoms, and optionally (c-2) an ethylene homopolymer. (c2) The melt flow rate, measured in accordance with ASTM D1238 at 190° C. under a load of 2.16 kg, is 0.1 to 10 g / 10 min. (c3) The proportion of the copolymer (c-1) in the ethylene polymer (C) is 40 to 100% by mass.

2. The adhesive resin composition according to claim 1, wherein the content of the ethylene polymer (C) is 12.5 to 30 parts by mass.

3. The adhesive resin composition according to claim 1 or 2, wherein the copolymer (c-1) has a melt flow rate (MFR) measured in accordance with ASTM D1238 at 230°C under a load of 2.16 kg of less than 6.0 g / 10 min.

4. the polyolefin (B) contains a structure derived from the unsaturated carboxylic acid and / or a derivative thereof in an amount of 0.01 to 5 mass % calculated as a structure derived from maleic anhydride, 3. The adhesive resin composition according to claim 1, wherein the polyolefin (b) contains 90 to 100 mol % of structural units derived from propylene.

5. A single-layer or multi-layer film comprising at least one layer comprising the adhesive resin composition according to claim 1 or 2.

6. A multilayer film comprising at least one layer comprising the adhesive resin composition according to claim 1 or 2, and at least one other layer which is a layer other than the layer comprising the adhesive resin composition, wherein the layer comprising the adhesive resin composition is in contact with the other layer.

7. A multilayer film comprising at least one layer comprising the adhesive resin composition according to claim 1 or 2, and at least one layer selected from a metal-containing layer, a polyolefin layer and a polar resin layer, wherein the layer comprising the adhesive resin composition is in contact with the layer selected from the metal-containing layer, the polyolefin layer and the polar resin layer.

8. 6. The monolayer or multilayer film according to claim 5, which is a film for packaging batteries.

9. The monolayer or multilayer film according to claim 5, which is an electrode sealing material for a lithium ion battery.

10. A method for producing a monolayer or multilayer film, comprising a step of melt-extrusion molding the adhesive resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Packaging material for battery

    JP2007273398A

  • Composite having composition layer and metal layer

    JP2020093428A

  • Adhesive resin composition and laminate

    JP2020111745A

  • Modified polypropylene composition and laminate using same

    WO2012077706A1

  • Laminate for battery

    WO2018180165A1